Association of non-alcoholic fatty liver disease and polycystic ovarian syndrome. Issue 1 (11th August 2020) - Asfari, Mohammad Maysara; Sarmini, Muhammad Talal; Baidoun, Firas; Al-Khadra, Yasser; Ezzaizi, Yamen; Dasarathy, Srinivasan; McCullough, Arthur
Abstract : Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder in women. Women with PCOS have androgen excess as a defining feature. They also have increased insulin resistance and obesity, which are also risk factors for non-alcoholic fatty liver disease (NAFLD). However, published data regarding PCOS as independent risk factor for NAFLD remain controversial. Therefore, we conducted this study to evaluate the association between PCOS and NAFLD using a large national database. Methods: We identified adult female patients (≥18 years) with PCOS using the National Inpatient Sample database between 2002 and 2014. The control group included patients who did not have a diagnosis of PCOS. Multivariate logistic regression analysis was performed to study the association of NAFLD with PCOS. Results: Out of a total of 50 785 354 women, 77 415 (0.15%) had PCOS. These patients were younger (32.7 vs 54.8; p<0.001) and more likely to be obese (29.4% vs 8.6%; p<0.001) compared with non-PCOS patients. However, the PCOS group had less hypertension (23.2% vs 39.8%), dyslipidaemia (12% vs 17.8%) and diabetes mellitus (18.1% vs 18.3%) (p<0.001 for all). Using multivariate logistic regression, patients with PCOS had significantly higher rate of NAFLD (OR 4.30, 95% CI 4.11 to 4.50, p<0.001). Conclusion: Our study showed that patients with PCOS have four times higher risk of developing NAFLD compared with women without PCOS. Further studies are needed to assess if specific PCOS treatments can affect NAFLD progression.